Hybridized enhancement of the SERS detection of chemical and bio-marker molecules through Au nanosphere ornamentation of hybrid amorphous/crystalline Si nanoweb nanostructure biochip devices. Issue 34 (11th August 2016) - Powell, Jeffery Alexander; Venkatakrishnan, Krishnan; Tan, Bo
Abstract : We report the fabrication of hybrid Si SERS nanobiosensor biochip devices. Abstract : We report the fabrication of hybrid Si SERS nanobiosensor biochip devices. The biochip exhibits a proposed hybridized SERS biomolecule sensing phenomenon with the creation of a SERS-active 3D amorphous/crystalline silicon nanoweb that has undergone nano-ornamentation with gold nanospheres. The underlying interconnected 3D hybrid Si nanospheroid network created by a laser-ion plume formation mechanism is nano-ornamented with gold nanospheres using a physical ion plasma deposition method to enhance the nano-Raman sensitivity of these nanostructures. We observe a tunable hybridized enhancement of analyte detection that is a result of the distinct paired SERS mechanisms from the active nano-hybrid Si nanoweb structure and the Au nanosphere ornamentation, a result which to date is yet to be reported for biosensing with SERS semiconductor materials. By linking the SERS enhancing effects of the base nano-hybrid Si nanoweb material with the SERS enhancing characteristics of gold nanospheres, we have observed a significant increase in sensitivity for the detection of chemical and bio-label molecules. Through manipulation of the hybrid Si nanoweb structure formation in coordination with the modulation of the nano-ornamentation process, we observe a hybrid nanostructured SERS-active nanomaterial that can be tailored specifically for biosensing applications. We report an observed enhancement factor (EF) for chemical molecule crystal violet (CV) of 3.0 × 10 7 and an EF value for the bio-label molecule rhodamine 6G (R6G) of 1.4 × 10 7 taking an Au nanosphere ornamented Si wafer as a benchmark.